Physical Fatigue as a Determinant of Occupational Accident Risk among Maritime Transport Workers - Ayu Lestari, Indah; Febriyanto, Kresna (Rifa'Institute, 2025)
Introduction: Work accidents in Indonesia’s maritime transport sector remain a major issue, often associated with physical fatigue due to prolonged working hours, insufficient rest, and exposure to extreme conditions. Objective: This study aimed to analyze the relationship between physical fatigue levels and occupational accident incidence among maritime transport workers in Samarinda and Balikpapan. Method: A cross-sectional study involving 136 crew members was conducted using accidental sampling. Physical fatigue was assessed with the Cumulative Fatigue Symptom Index (CFSI), and accident data were collected through a structured questionnaire. The Chi-square test was used for statistical analysis. Result and Discussion: High fatigue was reported by 51.5% of participants, and 67.6% had experienced work accidents. A significant association was found between fatigue and accident occurrence (p < 0.001), where workers with mild fatigue had a threefold lower risk of accidents (OR = 0.333; 95% CI: 0.237–0.469). Conclusions: Physical fatigue significantly increases the risk of occupational accidents among maritime transport workers, underscoring the importance of fatigue management and safety interventions in maritime operations.